The potential effects of COVID-19 lockdown and the following restrictions on the status of eight target stocks in the Adriatic Sea - Scarcella, Giuseppe; Angelini, Silvia; Armelloni, Enrico Nicola; Costantini, Ilaria; De Felice, Andrea; Guicciardi, Stefano; Leonori, Iole; Masnadi, Francesco; Scanu, Martina; Coro, Gianpaolo (Frontiers in Marine Science, 2022)
The COVID-19 pandemic had major impacts on the seafood supply chain, also reducing fishing activity. It is worth asking if the fish stock in the Mediterranean Sea, which in most cases has been in overfishing conditions for many years, may have benefitted from the reduction of the fishing pressure. The present work is the first attempt to make a quantitative evaluation of the impact of the COVID-19 related fishing effort reduction on the Mediterranean Sea fish stocks, focusing on the Adriatic Sea sub-areas. Eight commercially exploited target stocks (common sole, common cuttlefish, spot-tail mantis shrimp, European hake, red mullet, anchovy, sardine and deepwater pink shrimp) were evaluated with a surplus production model, separately fitting the data for each stock until 2019 and until 2020. Results for the 2019 and 2020 models in terms of biomass and fishing mortality were statistically compared with a bootstrap resampling technique to assess their statistical difference. Most of the stocks showed a small but significant improvement both in terms of biomass at sea and reduction in fishing mortality, except cuttlefish and pink shrimp, showing a reduction in biomass at sea and an increase in fishing mortality (only for common cuttlefish). After reviewing the potential co-occurrence of environmental and management-related factors, we concluded that only in the case of the common sole can be detected an effective biomass improvement related to the pandemic restrictions, because it is the target of the only fishing fleet whose activity remained far lower than the expectation for the entire 2020. We conclude by remarking that effort management based on fishing days reduction has many flaws, and alternative instruments such as spatial management and harvest control rules based on output control may help to improve the condition of Adriatic fisheries.